Knowledge and Awareness of Bio-Medical Waste Management among Senior Undergraduate and Specialist Dental Students: Cross-Sectional Study - Mohammad Ahmed Qasim Aljunaid1 , Aryo Dwipo Kusumo2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: There has been a universal rising in knowledge and awareness regarding the bio-medical waste management and the hazards related to it. Purpose: aims to determine and asses the knowledge as well as the awareness towards the management of bio-medical waste among senior undergraduate and specialist dental students in the Faculty of Dental Medicine, Universitas Airlangga, Surabaya - Indonesia. Materials and Method: The study was carried out by using a close-ended survey. The Population of the study consisted of 743 students. However, the taken sample was based on Lemeshow method that includes 130 senior undergraduate and 62 specialist students making a total of 192 participants. Statistical analysis was performed via descriptive statistical analysis and chi-square test. Results: This survey was shown that around 192 questionnaires were distributed of which (86%) returned and analyzed. It was seen that (58.7%) of senior undergraduate students and (87.1%) of specialist students, were having average knowledge of bio-medical waste management system in dental clinics. According to the Chi-square test analysis, it was seen there is a statistically significant P-value (p?0.05). Conclusion: Within the limitation of this study, we affirmed that there is a good level of knowledge and awareness of bio-medical waste management. In this present study, highly needed for continuing education and training programs to be conducted in dental teaching curricula in the Faculty of Dental Medicine